Combination pertuzumab, trastuzumab, and taxane for metastatic breast cancer after first progression: a single institution's experience. (April 2016) - Dao, Bao D; Ho, Hansen; Quintal, Laura N
Background: The addition of pertuzumab to trastuzumab and taxane therapy was shown to be an effective first-line treatment for patients with HER2-positive metastatic breast cancer. Objective: Describe the progression-free survival of pertuzumab, trastuzumab, and taxane therapy for previously treated HER2-positive metastatic breast cancer. Methods: This case-series reviews 19 patients with metastatic breast cancer receiving treatment with pertuzumab, trastuzumab, taxane after progression and exposure to previous lines of HER2-directed therapy. Progression-free survival and adverse effects such as changes in ejection fraction and episodes of neutropenic fever were assessed. Results: The median progression-free survival of pertuzumab, trastuzumab, taxane therapy for previously treated metastatic breast cancer was 4.1 months. The mean baseline left ventricular ejection fraction change experienced by patients was –1%. Neutropenic fever events were not encountered. Conclusions: Pertuzumab, trastuzumab, and taxane therapy seems to confer progression-free survival benefit for previously treated metastatic breast cancer. The use of the dual anti-HER2 antibodies, pertuzumab and trastuzumab, in addition to cytotoxic chemotherapy agents for previously treated metastatic breast cancer should be further evaluated.